INTRODUCED NETHERLANDS TULIP VARIETIES IN THE CLIMATE CONDITIONS OF THE PROVINCE CARE (British Journal of Global Ecology and Sustainable Development, 2023)
In the climatic conditions of the Namangan region, during the years 2018-2021, scientific research was conducted on irrigation, fertilization and agrotechnics of 16 types of tulips introduced from the Netherlands.